2020
DOI: 10.3390/sym12071162
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of the Magnetized Casson Nanofluid Propagating through an Exponentially Shrinking/Stretching Plate: Dual Solutions

Abstract: In this research, we intend to develop a dynamical system for the magnetohydrodynamic (MHD) flow of an electrically conducting Casson nanofluid on exponentially shrinking and stretching surfaces, in the presence of a velocity and concertation slip effect, with convective boundary conditions. There are three main objectives of this article, specifically, to discuss the heat characteristics of flow, to find multiple solutions on both surfaces, and to do stability analyses. The main equations of flow are governed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Based on a scale analysis, we put forward a standard boundary layer approximation on the unsteady MHD Casson nanofluid flow with heat and mass transfer and is governed by the following equations with the aforesaid assumptions and relevant boundary conditions 6,[24][25][26][27][28][29][30][31][32][33][34][35] :…”
Section: Mathematical Model Of the Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a scale analysis, we put forward a standard boundary layer approximation on the unsteady MHD Casson nanofluid flow with heat and mass transfer and is governed by the following equations with the aforesaid assumptions and relevant boundary conditions 6,[24][25][26][27][28][29][30][31][32][33][34][35] :…”
Section: Mathematical Model Of the Flowmentioning
confidence: 99%
“…Rafique et al 28 used a nonlinear inclined surface to numerically study the impact of Soret and Dufour effects on the nanofluid flow. Lund et al 29 performed a stability analysis on MHD Casson nanofluid through an exponentially stretching and shrinking sheet. Reza‐E‐Rabbi 30 used a finite difference method to study an unsteady MHD Casson nanofluid, taking into account the effects of Brownian motion and the thermophoresis parameter.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 𝐹(𝜂, 𝜏), 𝐺(𝜂, 𝜏), 𝐻(𝜂, 𝜏), and 𝐽(𝜂, 𝜏) all their derivatives are assumed small relative to 𝑓 0 (𝜂), 𝑔 0 (𝜂), 𝜃 0 (𝜂), and ∅ 0 (𝜂). Now, substituting the correlation (25) in Equations (20)(21)(22)(23)(24), we get the following resultant Linearized Eigenvalue Problem (LEVP) system as follows:…”
Section: Temporal Stability Analysismentioning
confidence: 99%
“…The shooting method was then adopted to solve the resultant ODEs and triple solutions were obtained. Some important effects of the MHD on fluid flow can be seen in these articles [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The flow over a stretching sheet has attracted significant attention in the last few years due to its unique nature and industrial applications. Different studies on stretching sheets can be found in detail in the papers [44][45][46][47][48][49]. Gosh et al [50] used the Tiwari and Das model to investigate the couple stress magnetite-water-based nanofluid motion near a bi-directional stretchable surface incorporating the effects due to non-linear thermal radiations.…”
Section: Introductionmentioning
confidence: 99%